PKM Budidaya Tanaman Obat Keluarga (TOGA) dan Pengolahannya untuk Meningkatkan Imun Tubuh di Masa Pandemi - Tresjia C Rakian; Waode Nuraida; Rian Arini; Andi Awaluddin; Muhidin Muhidin; Gusti Ayu Kade Sutariati; Sitti Leomo; Mani Yusuf (Prima Abdika : Jurnal Pengabdian Masyarakat, 2022)
Cultivation of medicinal plants in the garden system can meet the needs of increasing the immune system for the people of Jati Bali Village. The purpose of this community service activity is to provide knowledge to the community about the cultivation of medicinal plants and spices in the garden system as well as the manufacture of liquid organic fertilizer from household waste as an alternative to meeting the needs of increasing the immune system during a pandemic. Activities that have been carried out to achieve the objectives of the Internal Community Partnership Program (PKMI) are through mass and group outreach to partners, training, and plot demonstrations. Through this activity, partners in Jati Bali Village have been able to cultivate medicinal plants and spices in the dasa wisma garden system. Partners who are actively involved in the activity have been able to produce liquid organic fertilizer from household waste.